Generation Exodus : the fate of young Jewish refugees from Nazi Germany - Laqueur, Walter 1921-2018 (The Tauber Institute for the Study of European Jewry series, 2001)
This text is a generational history of the young people whose lives were irrevocably shaped by the rise of the Nazis. Half a million Jews lived in Germany when Hitler came to power in 1933. Over the next decade, thousands would flee. Among these refugees, teens and young adults formed a remarkable generation. They were old enough to appreciate the loss of their homeland and the experience of flight, but often young and flexible enough to survive and even flourish in new environments. This generation has produced such disparate figures as Henry Kissinger and "Dr Ruth" Westheimer. Walter Laqueur has drawn on interviews, published and unpublished memoirs and his own experiences as a member of this group of refugees, to paint a vivid and moving portrait of Generation Exodus.